Influence de certains facteurs abiotiques sur le rythme de nutrition des muges élèves en étangs - Udrea, Valerian (Cercetări Marine - Recherches Marines, 2026)
In the freshwater ponds, the Mullets have presented different feeding rates determined by following factors: transparence, temperature and oxygen. Low feeding rates were recorded where the water has presented a transparence under 0.1m, a temperature under 17°C and oxygen under 4mg O2/l. The highest feeding rates were obtained where the transparence was between 0.5-0.8m, the temperatures between 20-28°C and an oxygen between 4-85mg O2/l with a saturation of 70-120‰.